(untitled) (Journal of Management & Business, 2021)
The objectivthe revoe of this research work is to analyze the main causes for requesting The objectivthe revocation of the mandate for citizen participation, to know the respect and guarantee of the right to defend legal assumptions in the process of revocation of the mandate of any popularly elected authority, According to legal regulations, for this, the use of a descriptive and qualitative research was specified as a methodology in which the in-depth explanation of the phenomenon and the problem has been established in the most complete way possible, obtaining the results through observation documentary and in conclusion, we can affirm that all these citizen initiatives have all the inhabitants of the territory where said request is presented as a natural person.